Implementasi Skyline Query pada Sistem Rekomendasi Pemilihan Tempat Kuliner di Kota Depok, Bogor, dan Tangerang - Asqia, Misna; Munir, Sirojul (LPPM STT Terpadu Nurul Fikri, 2021)
In recent years, creative economic businesses in the form of culinary stalls have sprung up in various regions in Indonesia. A digital platform application for recommendations for picking regional superior culinary tours is likely to be highly beneficial to tourists in selecting the desired culinary location based on their tastes. There are three aspects as standards for culinary enterprises: product aspects, service aspects, and management aspects; these aspects can be a reference in one's preferences in choosing or determining a rating from a culinary business. This study uses the skyline query method to implement recommendations for selecting places to eat based on tourist preferences on four aspects of criteria: food, atmosphere, service, and health. The survey results through questionnaires from 169 respondents from Depok, Bogor, and Tangerang obtained 85.63% of respondents choosing places to eat based on service aspects, 77.42% health aspects, 73.99% atmosphere aspects, and 67.82% food aspects. The results of implementing the skyline query algorithm on a MySQL relational database system and a web-based application prototype obtained 100% of the functional applications running well.